Evaluation of the ophthalmic and dermal irritability of the OLEOMASAJE formulation - Maritza F. Díaz; Kendra García; Rosa I. Meneau; Yaíma Sánchez; Gastón García (GarVal Editorial Ltda., 2015)
Context: Ozonized vegetable oils present germicidal effects which can be used as active principle in different cosmetological compositions. The thematic about of the corporal massage advantage have been very treatment by aesthetics, dermatologic and consumers. OLEOMASAJE formulation content ozonized sunflower oil OLEOZON as active principle active which present moisturizer and conditioner effects. Aims: To determine the possible dermal and ophthalmic irritability effects of the OLEOMASAJE. Methods: The trial was conducted in rabbits and the techniques described in the standardized procedures of the work established by the Center of Biological Research and Evaluations from Pharmacy and Food Institute of Havana University were used according to Norma ISO 10993-10. The ethical principles of the Good Practices of Laboratory were fulfilled to avoid suffering to the animals during the experimentation. Male rabbits with body weight between 2.05 and 2.48 kg were used. In the skin and the ocular structures the effects were observed immediately after of the application at 1, 24, 48 and 72 hours. Draize´s scale was applied to evaluate skin and ocular structures lesions. Results: The OLEOMASAJE formulation does not irritate de skin of the assayed rabbits. However, the ocular structures irritability index was of 4.5 after of first hour to apply of product. These wounds were missing before of 24 hours to apply of product. Conclusions: The OLEOMASAJE formulation obeys the indispensable requirements for the acceptance as cosmetic product and for it is used in corporal massage.